2019
DOI: 10.1002/bem.22177
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of intermediate frequency magnetic field in Tg.rasH2 mice

Abstract: Although the likelihood of exposure to leaking intermediate frequency magnetic fields (MFs) from electronic devices, such as induction‐heating and wireless power transfer systems, has increased, biological data assessing the health risks associated with human exposure remain insufficient. We examined the carcinogenicity of a 20 kHz MF, a typical frequency produced by induction‐heating cookers, using a transgenic rasH2 mouse model. Twenty‐five male and female CByB6F1‐Tg(HRAS)2Jic mice were exposed to a 0.20 mT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
2
1
0
Order By: Relevance
“…Our study shows that continuous exposure to magnetic fields at 20 kHz and 360 μTesla does not cause significant changes in the body mass, the lymphatic tissue, and the incidence of tumors, respectively, in female mice. Our findings are in accordance with the previously published data, including evidence of the absence of carcinogenicity of magnetic fields in the CD-1 IGS mouse model [Lee et al, 2007;Kumari et al, 2017;Herrala et al, 2018;Kumari et al, 2018;Nishimura et al, 2019]. Additionally, Nishimura et al [2019] examined the carcinogenicity of a 20 kHz MF on a mouse model called Tg.rasH2 using shorter exposure times (26 weeks), again finding no evidence of carcinogenic effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study shows that continuous exposure to magnetic fields at 20 kHz and 360 μTesla does not cause significant changes in the body mass, the lymphatic tissue, and the incidence of tumors, respectively, in female mice. Our findings are in accordance with the previously published data, including evidence of the absence of carcinogenicity of magnetic fields in the CD-1 IGS mouse model [Lee et al, 2007;Kumari et al, 2017;Herrala et al, 2018;Kumari et al, 2018;Nishimura et al, 2019]. Additionally, Nishimura et al [2019] examined the carcinogenicity of a 20 kHz MF on a mouse model called Tg.rasH2 using shorter exposure times (26 weeks), again finding no evidence of carcinogenic effects.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in accordance with the previously published data, including evidence of the absence of carcinogenicity of magnetic fields in the CD-1 IGS mouse model [Lee et al, 2007;Kumari et al, 2017;Herrala et al, 2018;Kumari et al, 2018;Nishimura et al, 2019]. Additionally, Nishimura et al [2019] examined the carcinogenicity of a 20 kHz MF on a mouse model called Tg.rasH2 using shorter exposure times (26 weeks), again finding no evidence of carcinogenic effects. Another study in mice [Robertson et al, 1996] that exposed male and female animals to 10 kHz magnetic fields of up to 1 mT for 14 days or 90 days revealed no negative impact on the animals.…”
Section: Discussionsupporting
confidence: 92%
“…The WHO has emphasized that more research is needed on the potential health effects of exposure to this frequency [ 3 ] and suggested that more detailed parameters should be studied. Currently, several studies are addressing the biological effects of IF, including developmental and reproductive effects from maternal exposure [ 6 , 7 , 8 ], carcinogenic effects [ 9 ], and genotoxic effects [ 10 ]. However, most of these studies consider only a limited range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…This RF belongs to Group 2B on the carcinogenic hazard identification of IARC [14]. Many in vivo and in vitro studies have also been conducted on exposure to magnetic fields in the intermediate frequency (IF; 300 Hz to 10 MHz) range [15][16][17][18][19][20][21][22][23]. Most reports showed no effect after exposure to IF magnetic fields, although some studies have shown an increase in oxidative stress markers [20].…”
Section: Introductionmentioning
confidence: 99%